Fashion and Literature in Brazil: Considerations on the 19th Century Lexicon - Orsi, Vivian [UNESP]; Almeida, Marciele Cristina [UNESP] (Univ Fed Minas Gerais, Dept Filosofia & Ciencias Humanas, 2019)
Fashion, with its own language, establishes a group identity within the society and the period in which it is set. Moreover, it is a way of communication between an individual and the world around them. This research aims at the study of the lexicon of nineteenth-century fashion in Brazil, based on the theories of Lexicology and Fashion, on a collection of lexical items referring to clothes found in Memorias postumas de Bras Cubas (The Posthumous Memoirs of Bras Cubas), Machado de Assis (1994), and Luciola, Jose de Alencar (1988). The results of the reflection leave room for understanding of the social dynamics of the society of the time and of the establishment of the Brazilian Portuguese language independent from the continental variety..
Keywords: lexicon; fashion; literature; 19th century